Antiproliferative and anti-inflammatory properties of diindolylmethane and lupeol against N-butyl-N-(4-hydroxybutyl) nitrosamine induced bladder carcinogenesis in experimental rats. (June 2016) - Prabhu, B; Balakrishnan, D; Sundaresan, S
Introduction: Chemoprevention may involve perturbation of a variety of steps in tumor initiation, promotion, and progression. Objective: To investigate the antiproliferative and anti-inflammatory potential effects of diindolylmethane (DIM) and lupeol on experimental bladder carcinogenesis. Methods: Sixty healthy male Wistar rats were selected and randomly divided into six groups, with 10 rats in each group. Group I: control; group II: N -butyl- N -(4-hydroxybutyl) nitrosamine (BBN; 150 mg/gavage/twice a week) for 8 weeks, and then they were given 100 ppm concentrations of dimethylarsenic acid (DMA) in the drinking water for 28 weeks; group III: BBN + DMA + DIM (5 mg/kg body weight (b.w.)/day) treatment was started after BBN treatment, and it was orally administered for 28 weeks); group IV: BBN + DMA + lupeol (50 mg/kg b.w./day) treatment was started after BBN treatment, and it was orally administered for 28 weeks); and groups V and VI: DIM and lupeol treatment alone for 36 weeks. Bladder tissues were collected after 36th week study protocol for further analysis. Results: Our results revealed that DIM and lupeol treatment showed inhibition of tumor growth in the bladder by histopathological confirmations as well as significantly ( p < 0.001) increased the expression of phosphotensin (PTEN) and significantly ( p < 0.001) decreased the expression of tumor necrosis factor α, nuclear factor κβ (p65) were quantified using Western blot analysis. DIM and lupeol treatment significantly ( p < 0.001) decreased the levels of Cox-2 in bladder tissue samples and NMP 22 in urine samples were quantified using enzyme-linked immunosorbent assay method. Conclusion: Preventive DIM and lupeol administration act as potent Cox-2 inhibitors, which activates the tumor suppressor protein PTEN against experimental bladder carcinogenesis by antiproliferative and anti-inflammatory properties.